Agen Moderasi Di Ujung Jari: Pengelolaan Ruang Percakapan Digital (RPD) Di Tingkat Rukun Tetangga (RT) - Nesha Chania; Akbar NST; Habib Jatmika Imam; Abdullah Khusairi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research initiated the Digital Conversation Room (RPD) as a group communication medium to implement religious moderation at the Neighborhood Unit (RT) level. This idea was born after conducting research on RPDs managed at the RT level. The results of this research recommend the presence of moderation agents in conversation rooms at the RT level, as new personnel in carrying out programs of the Ministry of Religion of the Republic of Indonesia (Kemenag RI). This research uses a phenomenological approach by observing and examining RPD at the RT level and also religious moderation programs in Indonesia. The method used in this research was independent interviews with a number of RT heads based on categorization adjusted by the researcher, then supported by literature sources relevant to the research topic. The data analysis technique used is data reduction. The researcher summarizes the information obtained in the field and supporting sources into more detail, so that conclusions can be drawn. The result of this research is the birth of ideas for driving moderation agents that can be used by all RT heads in the Indonesian archipelago.